Research and Application of Fast Dynamic Response Algorithm for Thyristor Rectifier - TAO Hongliang; CHEN Jielian; ZHANG Min; CAI Yufeng; SUN Mao (Kongzhi Yu Xinxi Jishu)
Thyristor rectifier is the main type of power supply in the field of nuclear fusion plasma research, and it is the power source driving the coil to generate the magnetic field. The traditional feedback control algorithm has the problems of slow response speed, large overshoot and long stabilization time, and it is difficult to meet the technical requirements amid the rapid changes and complex control of plasma load. For this reason, a new feedforward and feedback fast dynamic response algorithm is designed in this paper. The algorithm calculates the commutation voltage drop of thyristor and the voltage drop on reactor and thyristor through quantitative analysis, and added a given reference value as the feedforward voltage. The trigger angle of thyristor is quickly calculated by using feedforward voltage control as the main method and feedback voltage control as the auxiliary method. The results of application in WEST divertor coil power supply of the French Atomic Energy Commission show that the new algorithm has very good fast dynamic response performance compared to the traditional feedback voltage control based algorithm without feedforward voltage control. The full power step response time of the power supply can reach within 2 ms from startup to stability, the response speed is improved by 90%, and at the same time, it can realize zero overshoot.